Implementasi Model Cooperative Learning Metode TGT Melalui Media Audiovisual Dalam Pembelajaran Aktivitas Ritmik Lompat Tali Di Sekolah Dasar - Saskia, Siti; Mahendra, Agus; Samini, Neneng (TEGAR: Journal of Teaching Physical Education in Elementary School, 2018)
This research’s aim is to improve the learning effectiveness of skipping rope as part of rhythmical activities with employing cooperative learning in TGT format. The participant of this research is Forth Grader of SDN 044 of Cicadas Awigombong, totalling 25 pupils. The study was conducted by Classroom Action Research format, elaborating two cycles, each of which consist of two actions, mingling cooperative model and audio-visual media, and its progress was measured by means of skipping rope skill test and semi-structured observational sheet. The collected data were analysed by percentage format so that the result can be summarized. The progress of skipping rope skill from initial observation to the last test were from 20% to 89 %, while the progress of cooperative skill from initial observation to the last action were from 38% to 95%. It can be concluded that the implementation of cooperative learning model (TGT format) combined with audio-visual media is effective in improving both the skipping rope and cooperative skill of the children of the 4th grade students of SDN 044 Cicadas Awigombong AbstrakPenelitian ini bermaksud melihat efektivitas pembelajaran lompat tali sabagi bagian dari aktivitas ritmik dengan menggunakan model kooperatif berformat TGT. Subjek penelitian adalah peserta siswa kelas IV SDN 044 Cicadas Awigombong, berjumlah 25 orang. Penelitian ini dilaksanakan dengan pendekatan Penelitian Tindakan Kelas, dengan mengelaborasi dua siklus, yang masing-masing terdiri dari dua tindakan, menggabungkan penggunaan model kooperatif dengan media audiovisual, dan kemajuannya diukur melalui tes lompat tali dan lembar pengamatan terstruktur. Data terkumpul dianalisis dan diolah dengan persentase sehingga dapat disimpulkan bahwa hasil observasi awal terhadap nilai kerjasama sebesar 20%, yang meningkat menjadi 89%. Demikian juga dalam hal keterampian lompat tali, yang hasil observasi awal sebesar 38%, meningkat  menjadi 95%. Kesimpulannya, implementasi model pembelajaran kooperatif metode TGT dengan bantuan media audio visual (video) memberikan pengaruh yang signifikan terhadap peningkatan keterampilan lompat tali dan kerjasama siswa kelas IV di SD Negeri 044 Cicadas Awigombong.